The study of the implementation of bridge management system in Sabah - Salinah Dullah; M.M. Fashius; Habibah Ghazali (Trans Tech Publications, 2015)
Bridge Management System (BMS) is an important tool which can help to manage huge number of bridges while efficiently utilizes limited fund for maintenance. Although major bridge failure is uncommon in Sabah, the concern for future adversity must be considered. The current status of the implantation of BMS in Sabah were studied and subsequently identifying the difficulties to implement the system locally. Interviews were done in Jabatan Kerja Raya, Headquarter and districts. Five locations were selected for observation. It was discovered that the implementation status of JKR BMS is still far from a successful implementation.